Exploration of Proteins Involved in Acquisition of Resistance to Cetuximab - Hironori Nakamura; Ayumu Nagamine; Hideaki Yashima; Takuya Araki; Koujirou Yamamoto (Universitas Padjadjaran (Unpad), 2019)
Anti-epidermal growth factor receptor (EGFR) monoclonal antibodies (Mabs) show high efficacy in about 50% of colorectal cancer (CRC) patients with wild-type KRAS. However, < 20% of patients with KRAS wild-type CRC have continued therapeutic effects with these agents, and acquired resistance to treatment has become a serious clinical problem. In this study, to clarify the factors related to acquisition of resistance to cetuximab (Cmab) and establish countermeasures against such acquired resistance, we conducted a comprehensive protein analysis via a proteomics approach using acquired resistance cell lines derived from Cmab-sensitive CRC cell lines and original cell lines. Cmab-acquired resistance cell lines were generated by continuous exposure of SW48 and C99 cell lines to Cmab. Expression of dCK and zinc finger and BTB domain-containing protein 41 (ZBTB41) increased more than 10-fold, and dual specificity protein phosphatase 3 (DUS3) expression decreased by less than 1/10 with acquisition of resistance to Cmab in both C99 and SW48 cell lines. Because overexpression of dCK is known as a positive indicator of efficacy of nucleoside analogs such as cytarabine or gemcitabine, it is considered that nucleoside analogs activated by dCK may be useful agents in treatment of cancers with acquired Cmab-resistance. In the future, we need to clarify the usefulness of these drugs for the treatment of Cmab resistant CRC and to assess the possibility of restoration of Cmab sensitivity by regulation of ZBTB41 and DUS3 expression.Keyword : cetuximab, colorectal cancer, acquired resistance, protein, dCK, ZBTB41